2007
DOI: 10.1002/jcb.21496
|View full text |Cite
|
Sign up to set email alerts
|

S100A6 (calcyclin) enhances the sensitivity to apoptosis via the upregulation of caspase‐3 activity in Hep3B cells

Abstract: S100A6 (calcyclin) is a small calcium-binding protein which has been implicated in several cellular processes such as cell cycle progression, cytoskeleton rearrangement, and exocytosis. Also the upregulation of S100A6 has been reported in a variety of tumors and linked to metastasis. However, exact intracellular roles of S100A6 related with apoptosis have not been clarified yet. Here we demonstrated that the upregulation of S100A6 enhances the cell death rate compared to the control under the apoptotic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 45 publications
(45 reference statements)
2
25
1
Order By: Relevance
“…In agreement with our observation that S100A6 is an anti-apoptotic gene, in a cholesteatoma cell line, high levels of S100A6 were associated with the lowest levels of apoptosis (11). However, several recent publications have shown that exogenously administered S100A6 at micromolar concentrations induces glioblastoma cell apoptosis by interacting with the receptor for advanced glycation end products (47), and exogenously introduced S100A6 to a human liver cell line (Hep3B and HepG2) potentiated apoptotic response of the calcium ionophore A23187 (48). These data demonstrate that the differential effects of S100A6 on apoptosis may be dependent on the specific cell type, the concentration of S100A6, and the preferential activation of one distinct signaling pathway as has been suggested for S100B (47,49).…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our observation that S100A6 is an anti-apoptotic gene, in a cholesteatoma cell line, high levels of S100A6 were associated with the lowest levels of apoptosis (11). However, several recent publications have shown that exogenously administered S100A6 at micromolar concentrations induces glioblastoma cell apoptosis by interacting with the receptor for advanced glycation end products (47), and exogenously introduced S100A6 to a human liver cell line (Hep3B and HepG2) potentiated apoptotic response of the calcium ionophore A23187 (48). These data demonstrate that the differential effects of S100A6 on apoptosis may be dependent on the specific cell type, the concentration of S100A6, and the preferential activation of one distinct signaling pathway as has been suggested for S100B (47,49).…”
Section: Discussionsupporting
confidence: 91%
“…However, we have noticed that the clone formation efficiency was lower in ADAR1-knockdown H9 cells than that in control cells (Supplementary information, Figure S1F). RNA-seq and RT-qPCR results further revealed that some key pro-apoptotic genes, such as S100A6 and BAX [31][32][33], were upregulated and the anti-apoptotic gene SFRP1 [34,35] was downregulated in ADAR1-knockdown H9 cells (Supplementary information, Figure S1G and Table S2), suggesting that ADAR1 deficiency can promote apoptosis of hESCs under certain stresses, such as enzymatic detachment. This is consistent with a previous report that cells cultured from ADAR1-deficient embryos exhibited increased apoptosis when a stress response was induced [24].…”
Section: Adar1 Knockdown Has Little Effect On Hesc Pluripotencymentioning
confidence: 98%
“…These two proteins are members of the S100 protein family and have been revealed to serve important roles in a number of tumorigenic processes, including apoptosis, cell differentiation, cell growth and cell cycle. The upregulation of S100-A6 has been demonstrated to enhance apoptosis and decrease cell viability by affecting caspase-3 activity in hepatocellular carcinoma cells (32). S100-A11 was identified to be involved in cell differentiation, cell cycle, cell growth and cell apoptosis processes.…”
Section: Discussionmentioning
confidence: 99%